2005
DOI: 10.1353/hpu.2005.0105
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Depression among Low-income Mexican Americans In Primary Care

Abstract: Between one and two thirds of depressive disorders go undetected in primary care settings. Four hundred ninety-six Mexican American primary care patients from high-poverty areas were screened for depressive symptoms, and 41% endorsed depressive symptoms. Eighty percent of screened patients with depressive symptoms agreed to structured diagnostic interviews and 90% of those interviewed met diagnostic criteria for one or more depressive disorders. Cases of depression detected through this systematic process were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Although the fully structured research interviews used in epidemiological surveys differ from clinical interviews, these findings may also have clinical implications. Clinicians should be aware that assessments of particular aspects of depression maybe affected by choice of the idiom used in a clinical interview (Kleinman, 2004;Neighbors et al, 1999;Schmaling and Hernandez, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fully structured research interviews used in epidemiological surveys differ from clinical interviews, these findings may also have clinical implications. Clinicians should be aware that assessments of particular aspects of depression maybe affected by choice of the idiom used in a clinical interview (Kleinman, 2004;Neighbors et al, 1999;Schmaling and Hernandez, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the fully structured research interviews used in epidemiological surveys differ from clinical interviews, these findings may also have clinical implications. Clinicians should be aware that assessments of particular aspects of depression maybe affected by choice of the idiom used in a clinical interview (Kleinman, 2004;Neighbors et al, 1999;Schmaling and Hernandez, 2005).On the other hand, correction for these differences in the way people responded to survey questions did not change the epidemiological conclusions. When we removed the questions that contributed to underestimation of depression among minorities and recalculated the prevalence estimates, the original findings were not altered.…”
mentioning
confidence: 99%
“…The same study emphasized, however, that clinician recommendation was the most commonly cited encouragement for cancer screening among minority women. Data indicate that physicians miss several opportunities during office visits and acute care visits to help their patients avoid disease and serious complications through undertaking preventative care including vaccination, cancer screening, dietary counseling, and screening for chronic conditions such as diabetes and depression (Stone et al, 2002; Agency for Healthcare Research and Quality, 2006;Schmaling & Hernandez, 2005).…”
Section: Correct Organizational and Logistical Deficienciesmentioning
confidence: 99%
“…Many Hispanics experience psychiatric disorders as somatic symptoms and prefer to seek care from primary care providers who may not recognize clinically significant depressive symptoms (Tarshis, Jutte, & Huffman, 2006) and are reluctant to record diagnoses of depression given that Hispanics are resistant to pharmaceutical therapies for mental health issues (Schmaling & Hernandez, 2005). Hispanic immigrants are much more likely to seek care if they are suffering from comorbid disorders (Vega, Kolody, & Aguilar-Gaxiola, 2001;.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…However, Breslau et al (2005) found that Hispanics had a lower lifetime prevalence of any mental disorder than non-Hispanic Whites based on data from the NCS among English-speaking households. Many studies, including our own, use clinical data that are derived from service utilization (see Caetano, Mora, Schaefer, & Marino, 1999;Schmaling & Hernandez, 2005;Wang et al, 2005). Since Hispanics are less likely to use mental health services, whether from lack of accessible treatment centers or services or culturally defined perceptions of mental health problems, data from service utilization are more likely to reflect underreporting of mental health issues than a survey that includes a diagnostic interview such as the CIDI.…”
Section: Background and Literature Reviewmentioning
confidence: 99%